The Effectiveness of Using the SCAMPER Programme to Learn the Basic Fundamentals of Futsal - Lawas, Noor Sabah (Pubmedia Jurnal Pendidikan Olahraga, 2024)
The current research aimed to identify the effectiveness of using the SCAMPER strategy to learn the research problem is to demonstrate the importance of the impact of the proposed intervention. The research problem addressed that the repeated failure of learners when performing the basic skills of the futsal game prompted the study of this issue and develop appropriate solutions through the development of exercises on the SCAMPER scrambler that will improve the basic skills of futsal. The research sample included students of the Department of Sport and Exercise Science, who numbered (30) students and were divided into two experimental and control groups, each group (15 students). (15) female students, and the researcher applied the research experiment using the methodology described above, and through the results, the researcher found that Scamper has a key role in developing creative abilities, developing independence to reach goals, and investing time and effort. The researcher recommended the need to emphasis the use of SCAMPER as a tool for learning how to play the game in the gym.